Mapping Agile HRM and Organizational Resilience: A Bibliometric Review - William Widjaja; Michael Michael; Hastuti Naibaho (Jurnal Manajemen Sains dan Organisasi, 2026)
Objective – This research aims to map scientific developments in Agile Human Resource Management (Agile HRM) and organizational resilience, and to identify intellectual structures, thematic clusters, and research evolution directions for the period 2010–2025. Design/Methodology/Approach – A bibliometric approach was employed by analyzing 1,000 articles retrieved from the Crossref database via Publish or Perish using combined keywords related to Agile HRM and organizational resilience. The selection process followed the PRISMA protocol and produced 235 eligible articles for analysis. VOSviewer was used to conduct descriptive analysis and to generate network visualization, overlay visualization, and density mapping in order to capture conceptual relationships and temporal dynamics. Findings – The results indicate a notable increase in publications since 2020 and reveal three dominant thematic clusters: (1) an agile methodology cluster, (2) a strategy and organizational systems cluster, and (3) an HR practice cluster emphasizing adaptability, collaboration, and employee engagement. Overlay visualization suggests an evolution of the research focus from a primarily technical orientation toward strategic integration and practical implementation of Agile HRM for strengthening organizational resilience. Implications – The study concludes that Agile HRM contributes meaningfully to strengthening organizations’ adaptive capabilities and long-term resilience. Theoretically, the findings extend Dynamic Capabilities, the Resource-Based View, and Contingency Theory by clarifying how HR agility mechanisms support resilience. Practically, the results offer guidance for organizations to develop agile HR practices as a foundation for sustained resilience.